Neuroprotective effects of PrxI over‐expression in an in vitro human Alzheimer's disease model. Issue 3 (22nd January 2013) - Cimini, Annamaria; Gentile, Roberta; Angelucci, Francesco; Benedetti, Elisabetta; Pitari, Giuseppina; Giordano, Antonio; Ippoliti, Rodolfo
Abstract Peroxiredoxins are ubiquitous proteins that recently attracted major interests in view of the strict correlation observed in several cell lines and/or tissues between different levels of their expression and the increased capacity of cells to survive in different pathophysiological conditions. They are recently considered as the most important enzymes regulating the concentration of hydroperoxides inside the cells. Most of neurodisorders such as Parkinson, Huntington, Alzheimer's diseases, and ischemic injury are characterized by conditions of oxidative stress inside cells. In these pathophysiological conditions, a strict correlation between cell survival and Prx expression has been found. In CNS all the Prx isoforms are present though with different expression pattern depending on cell phenotype. Interestingly, neurons treated with amyloid beta peptide (Aβ), showed an overexpression of PrxI. In this study, the neuroprotective effect of PrxI after Aβ exposure and the underlying mechanisms by which PrxI expression counteracts cell death was investigated in a well established human AD in vitro model. Taking advantage on cells transfected by a construct where human PrxI is fused with a Green fluorescent protein (GFP) at the C‐terminus, we report some events at the basis of cell survival after Aβ injury, suggesting possible new signal cascades dealing with the antiapoptotic effect of PrxI. The results obtained indicated a protective role for PrxI in counteracting Aβ injury by increasing cell viability, preserving neurites, and decreasing cell death. J. Cell. Biochem. 114: 708–715, 2013. © 2012 Wiley Periodicals, Inc.